Elements of Innovation Diffusion in the use of Hau Fo in Making Tea Bags - Neonufa, Samrid; Klau, Erni Raster; Selly, Frans Kristian; Taloim, Nory (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to determine the diffusion of innovations involving the use of hau fo in tea bag production. This study used a qualitative approach with a descriptive approach. This research was conducted at the Dapur Kelor Office of RSS Oesapa, Kupang City, East Nusa Tenggara. Six informants participated in this study. Data collection was conducted using three methods: observation, interviews, and documentation. The results indicate that the innovation carried out by Dapur Kelor aims to introduce the public to the fact that the moringa plant can be consumed in other processed forms, such as moringa tea bags, which have good nutrition for the body. This innovation was also carried out to improve the economy of moringa farmers and raise the economic standards of MSMEs. The marketing of the moringa tea bag innovation uses an application to sell processed products from Dapur Kelor in the Dapur Kelor Id store on Tokopedia, through Instagram, and directly to consumers. The decision-making process for the moringa tea bag innovation is considered successful because it has increased from year to year. Dapur Kelor itself employs SPGs (Sales Promotion Girls) and also collaborates with the Regional Government